Ice Age 2 : The Meltdown = Buz devri 2 - Saldanha, Carlos ([S.l.] : 20th Century Fox, 2006)
Manny, Sid, and Diego discover that the ice age is coming to an end, and join everybody for a journey to higher ground. On the trip, they discover that Manny, in fact, is not the last of the woolly mammoths.
3-6.
K-3.
Language : Turkish, English, Brazilian Portuquese, Latin Spanish, Russian, Estonian, Latvian, Lithuanian, Cantonese, Korean, Mandarin, Thai.
Subtitle : Turkish, English, Brazilian Portuquese, Latin Spanish, Russian, Estonian, Latvian, Lithuanian, Cantonese, Korean, Mandarin, Thai.
Keywords: Movie -- animated films; Movie -- Kids/Family.